Bangladesh - Dhaka : Improving Living Conditions for the Urban Poor - World Bank (2012)
This study on Bangladesh Dhaka-improving living conditions for the urban poor reflects a comprehensive look at poverty in Dhaka with an aim to provide the basis for an urban poverty reduction strategy for the Government of Bangladesh, local authorities, donors, and NGOs. While the needs in Dhaka are enormous, this study focuses on analyzing those critical for the poor - understanding the characteristics and dynamics of poverty, issues of employment, land and housing, basic services, and crime and violence. This analysis will provide a platform for developing recommendations for policy reform as Dhaka endeavors to meet the growing challenges and urgent needs of the urban poor. Each chapter concludes with a set of recommended priorities for poverty reduction.